Near-Infrared Reflectivity of Superconducting FeSe Thin Films - Yanmin Zhang; Wen Xu; Zhongpei Feng; Zefeng Lin; Kui Jin; Jie Zhang; Shun Zhou; Zhaojun Liu; Chen Guan; Tiandi Chen; Junqi Wang; Lan Ding; et al. (IEEE Photonics Journal)
We present an investigation on the intrinsic optical properties of superconducting FeSe thin films deposited on CaF2 substrates. It is found that the samples respond strongly to the near-infrared (NIR) irradiation in different temperature regimes. Thus, we are able to measure the optical reflectivity of the in-plane (ab-plane) thin films from room temperature to 5 K. A critical behavior near the superconducting transition temperature (Tc∼10 K) can be observed optically in the temperature-dependent reflectivity spectrum. We carry out the Kramers–Kronig analysis of the experimental data and discuss the basic optical properties of superconducting FeSe thin films in different structural phases above and below the transition temperature Ts∼100 K. By fitting experimental data with the Drude–Smith and Drude–Lorentz formulas, we obtain the key sample parameters such as the electronic relaxation time and dc conductivity. The interesting and important findings obtained from this study not only shed new light on the pairing mechanism in FeSe but also demonstrate that the NIR reflection experiment is a powerful and convenient optical technique for contactless characterization and investigation of superconducting thin film materials.